Household energy consumption behaviors during the Covid-19 pandemic in Mongolia - Dina Azhgaliyeva; Ranjeeta Mishra; Kamalbek Karymshakov (Asian Development Bank Institute (ADBI), 2021)
This investigation examines the impact of COVID-19 on households in Mongolia, particularly the choice of fuel for heating and cooking and awareness about harmful effects of indoor pollution due to the combustion of solid fuels for heating and cooking. This study uses publicly available MICS Plus survey data from UNICEF. MICS Plus is a longitudinal household survey with a sample of 2,000 representative households that collects information through telephone interviews. We compare data from a pre-COVID period (2018) and during the COVID-19 pandemic (December 2020). Our results show that households where the decision maker is female are more likely to have a clean source of heating-a district heating system. The results also show that a larger proportion of households switched to cleaner heating in the COVID-19 period. First, the share of households using central heating increased in 2020 to 26% from 19% in 2018. Second, the share of households using improved fuel for their heating requirements increased in 2020 as compared to 2018. Third, in December 2020, after the beginning of the COVID-19 pandemic, households were more likely to use district heating and manufactured space heaters than cooking stoves for heating compared to 2018.
Keywords: D14; G51; H12; H84; I10; I24; J6; 330; COVID-19; Mongolia; household survey; district heating; fuel choice; space heater